Marine composite sandwich plates under air and water blasts. (November 2017) - Hoo Fatt, Michelle S.; Sirivolu, Dushyanth
Abstract: Fluid-structure interaction solutions for the air and water blast response of marine composite sandwich panels with crushable foam cores are presented in this paper. Reflected and radiated acoustic pressure waves were introduced using Taylor's FSI method into Lagrange's equations of motion for the sandwich plate. In comparison to air blast, water-structure interactions diminished deflection and slowed down the response of the sandwich panel for a given pressure pulse loading. The predicted elastic-plastic transient response of the sandwich panel from the analytical model was shown to be fairly consistent results with ABAQUS Explicit. Pressure amplitudes to initiate damage in a sandwich panel with E-glass/Vinyl Ester facesheets and PVC H250 foam core were calculated under water blast/air back, water blast/water back, and air blast/air back conditions. It took significantly higher pressures to initiate damage in the panels under water blast/air back and water blast/water back conditions than in the air blast/air back plate because of fluid damping and higher plastic work dissipation in the core. A parametric study showed that on a per unit areal weight basis, panels with softer, more ductile foams were more blast resistant than panels with strong and stiff cores because of work dissipation during core plasticity. In the water blast cases, foam yielding was affected by transverse compression and not only transverse shear, as is usually case in air blast-loaded sandwich panels. Highlights: Solutions developed for air and water blast response of composite sandwich panels. Higher pressures to initiate damage because of fluid damping and core plasticity. Panels that experienced core crushing were more blast resistant. Core plasticity in panels under water blast is multi-axial.